2012
DOI: 10.1530/rep-12-0032
|View full text |Cite
|
Sign up to set email alerts
|

Luteal maintenance of pregnancy in the African elephant (Loxodonta africana)

Abstract: The ovaries of eight African elephant foetuses and their mothers between 2 and 22 months of gestation, and those of two cycling and two lactating elephants, were examined grossly, histologically and immunocytochemically, with emphasis on the development and regression of accessory corpora lutea (CL) of pregnancy and the steroidogenic capacities of the accessory CL and the foetal ovaries. The results supported recent findings that the accessory CL form as a result of luteinisation, with and without ovulation, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Some follicles are apparently so sensitive to the luteinizing factors that they respond before ovulation takes place, developing the luteinization of non-ovulated follicles [Stansfield & Allen, 2012]. Some follicles are apparently so sensitive to the luteinizing factors that they respond before ovulation takes place, developing the luteinization of non-ovulated follicles [Stansfield & Allen, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some follicles are apparently so sensitive to the luteinizing factors that they respond before ovulation takes place, developing the luteinization of non-ovulated follicles [Stansfield & Allen, 2012]. Some follicles are apparently so sensitive to the luteinizing factors that they respond before ovulation takes place, developing the luteinization of non-ovulated follicles [Stansfield & Allen, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Formation of accessory CL occurred both in pregnant and non-pregnant females in the luteal phase. Some follicles are apparently so sensitive to the luteinizing factors that they respond before ovulation takes place, developing the luteinization of non-ovulated follicles [Stansfield & Allen, 2012]. In the pregnant red uakari monkey, the presence of accessory CL resulted in a contribution up to 30% of the total luteal volume but was not related to the progress of pregnancy, suggesting a probable relation with the particular activity of the functional CL in each pregnant female [Rowlands et al, 1970].…”
Section: Discussionmentioning
confidence: 99%
“…Although degeneration of large luteal cells was observed in late compared with earlier pregnancy stages, they still stained positive for 3b hydroxysteroid dehydrogenase (an enzyme important for the biosynthesis of progesterone from pregnenolon) in CL even in near term pregnancy. However, compared with the first half of gestation, the staining was more patchy and not as uniform, implying reduced luteal secretory capacity [24]. This may be reflected in flattening serum progestagen concentrations during the second half of gestation as denoted in other studies [32,33].…”
Section: Discussionmentioning
confidence: 75%
“…Also, no chorionic gonadotropin and no endometrial cup-like structures could be identified in the gravid elephant uterus [4], suggesting that elephants pursue a different strategy compared with the mechanism of acCL formation in the pregnant mare. There is evidence that the foetal gonads of both genera may contribute to circulatory progestagen levels of the female elephant in late gestation, because, similar as in the foetal horse, the gonads enlarge from mid gestation and stain positive for 5a-reduced pregnanes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that African elephants developed an alternative solution to a luteo -placental shift by prolonging P4 production in the CL. Indeed it has been shown that, despite being mono-ovulatory, elephants produce accessory CLs that luteinize without ovulation and maintain P4 levels throughout gestation (Lueders et al 2012;Stansfield and Allen 2012). This is particularly interesting as the accessory corpora lutea have been found in several other species, such as horse and several monMammals U t e r in e m o t il it y G la n d u la r s e c r e t io n N o u r is h m e n t Birds, reptiles Monotremata Marsupialia I m p la n t a t io n E x t e n d e d p r e g n a n c y I n f la m m a t o r y p a r t u r it io n I n f la m m a t o r y s u p p r e s s io n Placental mammals keys; however, in these species, the P4 production in later stages of gestation is primarily placental.…”
Section: Pregnancy Pre-and Postluteolysismentioning
confidence: 99%